ANALISIS PRINSIP KESOPANAN PADA FILM JUSTICE HIGH MODEL GEOFFREY LEECH - Rahman, Lusiana; Emy Rizta Kusuma (BASA Journal of Language & Literature, 2024)
ABSTRACT This research aims to describe the explanation and form of the principles of politeness which are divided into several maxims in the Korean short film Justice High. The data collection methods used are the proficient free-involved listening technique (SBLC) and note-taking technique as an advanced technique. The data analysis method uses the technique of selecting determining elements. The research results consist of examples and discussion of the six maxims of politeness in the Korean short film Justice High, namely a) maxim of wisdom, b) maxim of acceptance, c) maxim of generosity, d) maxim of humility, e) maxim of compatibility, f) maxim of sympathy. The principle of politeness is viewed from the politeness scale according to Geoffrey Leech.